The way back home [videorecording (DVD)] - Badiyi, Reza S.; Harris, Julie, 1925-2013; Dee, Ruby; Deezer D. (Back Home Productions, 2008)
New York attorney Spencer Krane arrives in rural Florida to check on his grandmother, who has suffered a stroke. What begins as a brief visit becomes more of a journey of consequence. It is his time spent with his grandmother and her best friend that makes him realize he must come to terms with his past.